(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Our study explored the use of alginate-TiO₂ nanoparticles to effectively remove pesticide residues from water. We synthesized alginate-TiO₂ nanoparticles and characterized them using XRD, SEM, EDS, TEM, and FTIR. We then evaluated their ability to degrade four common bentazone residues in aqueous solutions under various sunlight conditions. Sterile buffer water solutions (pH 4, 7, and 9) containing 1 mg/L bentazone were prepared in a single replicate and stored in clear glass bottles. The bottles were sealed, covered with aluminum foil, and kept in direct sunlight. At periodically, the samples were tested for bentazone concentration using a validated HPLC method. On day 10, the photolysis test showed that 4.21%, 6.83%, and 15.28% of the bentazone had been hydrolyzed in the pH-4, pH-7, and pH-9 buffers, respectively. On day 2, the photocatalysis test using nanocatalyst revealed that 89.20%, 90.26%, and 97.12% of the bentazone were catalyzed, respectively. According to the findings, nanocatalyst is an effective decontaminating agent for removing pesticide residues from water. Alginate-TiO₂ nanocatalyst gives cost-effective, efficient, and environmentally friendly alternatives to traditional decontamination methods. Our study suggests that alginate-TiO₂ nanocatalyst is a promising nanomaterial for removing pesticide residues from water, with potential applications in wastewater treatment and environmental remediation. We hope that our findings will encourage further research on this issue and contribute to the development of sustainable and environmentally friendly solutions for enhancing water quality.